A Study of the Effectiveness of Blackboard Collaborate for Conducting Synchronous Courses at Multiple Locations - Guillermo Tonsmann (Park University, 2014)
This paper discusses the effectiveness of the videoconferencing software Blackboard Collaborate for carrying out instruction at college level to students attending classes synchronously at multiple locations. The paper describes the motivation for this study, a brief literature review on the subject, the methodology used, and the results obtained. The main conclusion of this study is the confirmation that synchronous instruction, in general, and Blackboard Collaborate, in particular, is an effective environment for tuition of students at a distance. Based on this study, several recommendations to be used in synchronous education are provided.